Territorial Development in Argentina : Using Differentiated Policies to Reduce Disparities and Spur Economic Growth - World Bank (World Bank, Washington, DC, 2020)
The National Constitution puts forward an ambitious goal for the Federal Government: a balanced territorial development; this promise has yet to be fulfilled. Within a cooperative federalism structure - where power-sharing does not always lead to clear separation of responsibilities between federal and provincial governments - Argentina struggles with overlaps in responsibilities and lack of defined roles across different government levels, which makes it difficult to coordinate policies to close territorial development gaps.